Bullying dalam Drama Korea (Analisis Resepsi dalam Drama Korea True Beauty 2020) - Rivga Agusta; Elvira Wahyuni (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This study analyzes the audience’s meaning of the bullying’s message contained in the Korean drama series entitled True Beauty. Audience reception studies see that the audience is a communication element that actively receives and interprets messages transmitted by the media, including the drama series True Beauty. True Beauty is one of the best and popular Korean dramas adapted from a Korean webtoon series entitled The Secret Of Angel. This drama series explores the phenomenon of bullying that occurs in the school environment based on the factor of physical beauty. The purpose of this research is to find out how Indonesian teenage audiences perceive bullying scenes in the 2020 Korean drama True Beauty. The data in this study were obtained through an in-depth interview process with 6 Indonesian teenage audiences, namely 5 female teenagers and 1 male teenager. The research method used is the reception analysis method on Stuart Hall's encoding-decoding theory with a descriptive qualitative approach. In selecting informants in this study using purposive sampling technique which includes people who will be selected based on predetermined characteristics. The results of this study are that there are 5 informants in the dominant hegemony position, 4 people are in the negotiation position and 1 person is in the opposition position.